Odpowiedź:
A=x^2 - 3x+1
B= - 4x^2 - 3
C= 6x+12
D= - 3x^2 - 5x+2
1. A+B+C
x^2 - 3x+1 - 4x^2 - 3+6x+12= - 3x^2+3x+10
2. B - D - A
- 4x^2 - 3 - ( - 3x^2 - 5x+2) - (x^2 - 3x+1)= - 4x^2 - 3+3x^2+5x - 2 - x^2+3x - 1=
- 2x^2+8x - 6
3. A - C+D
x^2 - 3x+1 - ( 6x+12)+( - 3x^2 - 5x+2)=x^2 - 3x+1 - 6x - 12 - 3x^2 - 5x+2=
- 2x^2 - 14x - 9
4. D - A - B
- 3x^2 - 5x+2 - (x^2 - 3x+1) - (- 4x^2 - 3)= - 3x^2 - 5x+2 - x^2+3x - 1+4x^2+3=
- 2x+4
5. C+B - A
6x+12- 4x^2 - 3 - (x^2 - 3x+1)=6x+12- 4x^2 - 3 - x^2+3x - 1= - 5x^2+9x+8
Szczegółowe wyjaśnienie: